Mystery Box Plant: A Gamified Meaningful Learning Approach to Enhancing Student's Green Affective Within Merdeka Belajar Curriculum Framework - Andiyani, Razni Yukti; Machfiroh, Runik; Rahman, Yanuar (Riviera Publishing, 2025)
The Merdeka Belajar curriculum and Green School guidelines emphasize project-based learning as a vehicle for cultivating environmental responsibility. However, in practice, students often exhibit low green affective responses and struggle to care for plants in classroom projects—an issue observed during preliminary fieldwork at SMPN 1 Warureja Tegal. To address this, the study aimed to design a meaningful and engaging gamified module that fosters environmental awareness through experiential learning. Employing a design thinking approach, the Mystery Box Plant game was developed, wherein students receive unidentified plant seeds and and must nurture them until growth allows identification. The element of curiosity, paired with real-time observation, invites deeper reflection on the care process. Students can only “win” by successfully growing and identifying their plant—thus linking responsibility with reward. Pre-test and post-test instruments were used to assess attitudinal change. Results indicate the module not only increased student engagement and responsibility in plant care but also enhanced their understanding of why environmental stewardship matters. By integrating meaningful learning strategies, the game facilitates the internalization of ecological values and encourages the formation of a sustained, affective mindset toward environmental care—advancing both curricular goals and long-term behavioral change.